2022
DOI: 10.1155/2022/1734049
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: An Updated Review of Epidemiology, Clinicopathology, and Treatment

Abstract: Male breast cancer (MaBC) is a rare clinical entity, which makes up approximately 1% of all breast cancers. However, the incidence of MaBC has been steadily increasing over the past few decades. The risk factors for MaBC include age, black race, family history of breast cancer, genetic mutations, liver cirrhosis, and testicular abnormalities. The majority of patients with MaBC present with painless lumps, and about half of the patients have at least one lymph node involved at the time of diagnosis. The treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 117 publications
2
25
0
Order By: Relevance
“…In conclusion, our study results continue to pursue the overall objective of better understanding genetic predisposition to mBC for developing appropriate clinical approaches for sex-specific risk prediction, which could lead to more targeted screening and treatment programs for male PV carriers. It remains to be determined whether the germline mutation status in BRCA1/2, ATM, CHEK2 and PALB2 predicts favourable or unfavourable targeted therapy response in mBC patients, e.g., regarding PARP or CDK4/6 inhibitors [38].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study results continue to pursue the overall objective of better understanding genetic predisposition to mBC for developing appropriate clinical approaches for sex-specific risk prediction, which could lead to more targeted screening and treatment programs for male PV carriers. It remains to be determined whether the germline mutation status in BRCA1/2, ATM, CHEK2 and PALB2 predicts favourable or unfavourable targeted therapy response in mBC patients, e.g., regarding PARP or CDK4/6 inhibitors [38].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 60 male breast cancer specimens with a familial background, Deb et al [ 84 ] also found no evidence of CDH1 gene methylation in this special subgroup of human breast cancer using HRM. Male breast cancer makes up approximately 1% of all human breast cancer cases [ 85 ].…”
Section: In Breast Cancermentioning
confidence: 99%
“…Invasive ductal carcinoma (IDC) is the most prevalent subtype of breast cancer, accounting for approximately 80% of all diagnosed cases in women of all ages and 85% of male breast cancers 8 , 9 . Invasive lobular carcinoma (ILC), the second most common subtype, accounts for 10-15% of all breast cancers 10 .…”
Section: Introductionmentioning
confidence: 99%